2016
DOI: 10.1111/jdi.12498
|View full text |Cite
|
Sign up to set email alerts
|

Ideal glycated hemoglobin cut‐off points for screening diabetes and prediabetes in a Chinese population

Abstract: Aims/IntroductionThe aims of the present study were to evaluate the diagnostic value of fasting plasma glucose, 2‐h postload plasma glucose and glycosylated hemoglobin (HbA1c) measurements in the screening of diabetes and prediabetes, and to determine the cut‐off point of HbA1c in the diagnosis of diabetes and prediabetes in a Chinese population.Materials and MethodsA total of 7,611 individuals aged 40 years or older, who did not have a prior history of diabetes, were randomly selected in the Changchun area. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
3
18
1
Order By: Relevance
“…This should then result in a significant reduction in the burden of testing on both patients and testing facility staff and resources. On the other hand, another recent study evaluated the diagnostic value of HbA1c measurements in screening of diabetes and prediabetes, and determine the cut-off point of HbA1c in a Chinese population (Liu et al, 2016). The results suggested an optimal HbA1c cut-off point of 6.3% in screening diabetes, consistent with a previous study, the authors also proposed an ideal HbA1c cut-off point of 5.8% in screening prediabetes.…”
Section: Discussionsupporting
confidence: 80%
“…This should then result in a significant reduction in the burden of testing on both patients and testing facility staff and resources. On the other hand, another recent study evaluated the diagnostic value of HbA1c measurements in screening of diabetes and prediabetes, and determine the cut-off point of HbA1c in a Chinese population (Liu et al, 2016). The results suggested an optimal HbA1c cut-off point of 6.3% in screening diabetes, consistent with a previous study, the authors also proposed an ideal HbA1c cut-off point of 5.8% in screening prediabetes.…”
Section: Discussionsupporting
confidence: 80%
“…accuracy of HbA1c measurements as a criterion for diabetes diagnosis had not been completely evaluated and unanimously accepted. [30][31][32] The recommended cut-off value of HbA1c ≥6.5% was reported to have a different sensitivity of risk compared with the oral glucose tolerance test among Chinese individuals. [33][34][35] Several other studies [36][37][38][39][40][41] questioned the single HbA1c cut-off value for a diabetes diagnosis because of the absence of agespecific criteria.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that using HbA1c and a cut‐off of 6.5% as a screening test for DM had a lower sensitivity (83.6%) and higher specificity (83.2%; Table ) in Chinese adults than in Malays and Indians (sensitivity 86.7–87.5%, specificity 77.6–80.7%), similar to results published by Sabanayagam et al These sensitivity and specificity results are similar to those reported by Wang et al who found that HbA1c at a cut‐off of 6.5% had a high sensitivity (80.6%) and specificity (86.9%) for detecting diabetic retinopathy. However, many studies on Chinese subjects recommended lower cut‐offs values, such as 5.6%, 5.8%, 6.2%, and 6.3%, for diagnosing DM, because these studies did not have repeat testing to confirm the diagnosis of DM.…”
Section: Discussionmentioning
confidence: 99%